A COMPARISON STUDY OF BIOPOLYMER WITH ALUM IN THE TREATMENT OF WATER - MOHD LAZI , MOHAMAD HAFIDZ (IRC, 2016)
There are various types of water treatment plants operating all around the world. Basically, conventional water treatment used coagulation and flocculation process in order to remove colour and the turbidity of the water. There are various type of coagulants and flocculants which are natural, chemical and polymers. Nowadays, wastewater treatment by natural polymers is being increasingly advocated. In this study, commercial polygalacturonic acid is used as biopolymer in water treatment process to evaluate the treatment efficacy in order to compare with alum. The characterization analyses are required for better understanding of the biopolymer.